Data for: Effects of insecticide treatment against blue stem weevil (Ceutorhynchus sulcicollis) and cabbage stem weevil (C. pallidactylus) on crop injury and yield in winter oilseed rape (Brassica napus) - Lundin, Ola (Swedish University of Agricultural Sciences, 2025)
We conducted five field experiments in two cropping seasons, where we tested pyrethroid insecticide application in autumn targeting Ceutorhynchus sulcicollis, in spring targeting C. pallidactylus, as well as combined applications in autumn and spring targeting both species. We evaluated stem injury, emergence of the new generation of weevils and crop yield and oil content. The dataset contains stem weevil injury (184 rows), pod injury (92 rows), weevil emergence (92 rows) and yield data (72 data rows).

The Swedish Board of Agriculture (Jordbruksverket) has monitored insects in the field locations and contributed to data collection concerning the insects and their injuries to the crop. The Rural Economy and Agricultural Societies (Hushållningssällskapet) has managed and harvested the experiements, and provided yield data.

More information about the data can be found in the readme.txt. file.

Vi genomförde fem fältförsök under två odlingssäsonger där vi testade applicering av pyretroid-insekticider på hösten mot Ceutorhynchus sulcicollis, på våren mot C. pallidactylus, samt kombinerad applicering på hösten och våren mot båda arterna. Vi utvärderade stamskador, uppkomsten av den nya generationen vivlar samt skörd och oljehalt. Data innehåller vivelskador i stjälkar (184 rader), skador på skidor (92 rader), uppkomst av vivlar (92 rader) och skördedata (72 datarader).

Jordbruksverket har övervakat insekter på försöksplatserna och bidragit till datainsamlingen gällande insekterna och deras skador. Hushållningssällskapet har skött och skördat experimenten samt bidragit med skördedata.

Mer information om data finns i filen readme.txt.
Data för: Effekter av insekticidbehandling mot blåvingad rapsvivel (Ceutorhynchus sulcicollis) och fyrtandad rapsvivel (C. pallidactylus) på skador och skörd i höstraps (Brassica napus)
Keywords: plant production; växtodling; crop protection; växtskydd; crop production; ceutorhynchus sulcicollis stephens, 1829; ceutorhynchus pallidactylus (marsham, t., 1802); brassica napus l.; pollen beetle; rapsbagge; blue stem weevil; blåvingad rapsvivel; cabbage stem weevil; fyrtandad rapsvivel; brassica pod midge; skidgallmygga; Brassicogethes aeneus; Dasineura brassicae; Ecology; Ekologi; Agricultural Science; Jordbruksvetenskap